THE IMPLEMENTATION OF DUAL PATHWAY CREATIVITY MODEL IN TOURISM SECTOR IN WEST SUMATRA - Zona, Mega Asri; Adrian, Arif (Hasanuddin Economics and Business Review, 2019)
This research examined the implementation of the Dual Pathway Creativity Model (DPCM) as a function of cognitive flexibility and cognitive persistence in employees working at companies engaged in the tourism sector in West Sumatra. Dual Pathway Creativity Model (DPCM) suggests a more comprehensive theory about employee creativity. DPCM argues that a flexible and pleasant environment can encourage flexibility and creativity. However, problems and a less flexible environment might also encourage creativity, but through a different process compared to a flexible environment. This research used a purposive sampling technique with 96 respondents, consisting of employees working in the tourism sector. The results showed that cognitive flexibility had a positive effect on employee creativity in the tourism sector in West Sumatra, while cognitive persistence had a negative effect on employee creativity in the tourism sector in West Sumatra.